PENYEBAB TERJADI KECEMASAN PADA IBU MENYUSUI: SCOPING REVIEW - Wulan Wijaya; Devi Yulianti (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2022)
Background: Pregnancy and childbirth are two major events in a woman's life. The postpartum period is a time of risk for the emergence of postpartum depression in the mother. The birth of a baby requires women to play the roles and responsibilities of women. Thus, the postpartum period is a time of risk for the emergence of maternal postpartum depression. Methods: This study uses a scoping review methodology. This study combines knowledge and information related to current assumptions regarding the factors that influence exclusive breastfeeding. This study emphasizes breastfeeding anxiety factors such as breastfeeding initiation, breastfeeding duration and identifies a total of 6 articles, which were reviewed and summarized in a narrative manner. Results: The findings of this study indicate that breastfeeding anxiety can influence mothers to give breast milk optimally. Family history of illness, lack of family support, lack of support from health workers and lack of knowledge of mothers are factors that cause breastfeeding anxiety. Conclusion: To reduce maternal anxiety while breastfeeding, immediate follow-up is needed to reduce these things. and can be used as input for policy makers, health workers and service users.